2014
DOI: 10.1139/cjfas-2013-0545
|View full text |Cite
|
Sign up to set email alerts
|

Weak effects of a microsporidian parasite on mottled sculpin in Michigan streams

Abstract: Despite the widespread occurrence of microsporidian parasites in vertebrates and many invertebrates, research regarding their effects on wild populations remains uncommon. We used several metrics of individual growth, condition, and population characteristics to evaluate the effects of a microsporidian infection (Glugea) on six infected populations of mottled sculpin (Cottus bairdii) compared with 10 nearby uninfected populations. Infected individuals (n = 129) were significantly heavier in each age class when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…High prevalence can be maintained for multiple years as shown by Seven Mile Creek, where prevalence ranged from 69 to 93% between 2007 and 2011. Prevalence can also fluctuate substantially; in 2007, prevalence in Silver Creek sculpin was 11% but reached 75% in 2011 (Homola et al 2014). However, prevalence in age-0 fish was very low.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…High prevalence can be maintained for multiple years as shown by Seven Mile Creek, where prevalence ranged from 69 to 93% between 2007 and 2011. Prevalence can also fluctuate substantially; in 2007, prevalence in Silver Creek sculpin was 11% but reached 75% in 2011 (Homola et al 2014). However, prevalence in age-0 fish was very low.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, any negative effects on individuals could be significant at the population level given the higher infection intensity in females and the high prevalence in general. However, work on these populations by Homola et al (2014) suggests that individual-and population-level effects are weak. While studies of rainbow smelt populations from multiple locations, including Lakes Erie and Ontario, showed that G. hertwigi reduced reproduction and increased mortality (Chen & Power 1972, Nepszy & Dechtiar 1972, Scarborough & Weidner 1979, models indicated no correlation between infection prevalence and smelt recruitment in Lake Erie over a 20 yr study (Henderson & Nepszy 1989).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The data indicated that C. aleuticus (but not C. cognatus ) with cestodes were heavier for their L T (after removal of the cestodes themselves from the fish) than conspecifics without cestodes, although L T at age did not differ in either species. This effect in condition factor was unexpected but consistent with the weak and very mixed effects of a microsporidian parasite on growth and condition in a different sculpin species (Homola et al , ).…”
Section: Counts Of Sculpins Cottus Aleuticus and Cottus Cognatus In Ementioning
confidence: 99%